Navigating the transition of care in patients with inborn errors of immunity: a single-center’s descriptive experience - Mejía González, María Alejandra; Quijada Morales, Patricia; Escobar, María Ángeles; Juárez Guerrero, Alba; Seoane-Reula, María Elena (Frontiers in Immunology, 2023)
The transition from pediatric to adult care is a critical milestone in managing children, especially in those with complex chronic conditions. It involves ensuring the patient and family adapt correctly to the new phase, maintaining continuity of ongoing treatments, and establishing an appropriate followup plan with specialists.information available regarding patients with PID associated with syndromic features, we share our experience in this issue as a Primary Immunodeficiencies Unit that is a National Reference Center for PID, and propose a guide to achieve an adequate and successful transition to adulthood in these patients, especially in those with associated syndromic features.